Value of Interventional Radiology: Past, Present, and Future - Doherty, Michael G. (Seminars in Interventional Radiology, 2019)
Interventional radiology (IR) has had immense growth in importance and value over the last several decades from its founding in the mid-20th century. IR procedures have been widely adopted and an era of IR clinical expertise is upon us. Despite this, there is a perception that IR is simply an imaging study to be ordered and that IR physicians are expendable. This article attempts to explore that. Questionnaires were sent to other specialties and administrators asking key questions regarding the value of IR as a specialty, both for procedural and consultative expertise as well as their thoughts on the future of IR. Answers varied, but consistent opinions were observed that IR is extremely valuable, both procedurally and consultatively, and that expansion of IR services is likely. IR is extremely valuable given its impact on healthcare (lessening morbidity, decreasing length of stay, improving cost) and although there is some misperception of this value, other specialties and administrators understand it well. Newer generations of IR physicians are poised to become even more impactful if they continue to expand their clinical presence.
Keywords: interventional radiology; value; economic impact